Effect Reduction of Hardware impairment on the NOMA systems - Beddiaf Safia (My University, 2023)
The rapid expansion of wireless communication systems has ushered in a new era marked by soaring demands for faster data rates, reduced latency, and improved spectral efficiency. To meet these demands, the Non-Orthogonal Multiple Access (NOMA) system has emerged as a game-changing technology. NOMA enables multiple users to share the same time-frequency resources, significantly enhancing system capacity and efficiency. Within NOMA, the power domain (PD-NOMA), where users share resources with different power allocation coefficients, has attracted particular interest. This approach employs successive interference canceler (SIC) to mitigate interference and has great potential for applications in 5G and beyond, leading to extensive research on its achievable rates and outage probabilities. In real communication systems, transceivers play a pivotal role by facilitating both the transmission and reception of signals. However, due to the intricate nature of their internal components and the inherent complexity of the manufacturing process, it is quite common for transceivers to exhibit hardware imperfections and non-ideal behavior. Several contributing factors give rise to this non-ideal operation, particularly in radio frequency (RF) transceivers. These hardware impairments (HWI) manifest across various stages of the transceiver's operation, non-linear behavior in high-power amplifiers, the presence of phase noise, and imbalances in the in-phase and quadrature (I/Q) components within the RF front-end. The motivation for our research stems from two primary concerns: NOMA and HWI. Our work is driven by the objective of exploring and understanding the performance such as capacity, outage probability (OP), ergodic capacity (EC), and bit error rate (EC) of NOMA systems operating in the presence of HWI. This research seeks to provide realistic conditions, where hardware imperfections can significantly impact the system's overall efficiency and reliability. By addressing these critical issues, our study aims to contribute to the enhancement of NOMA-based communication systems and their practical implementation in a range of applications. In the initial segment of this thesis, we delve into the impact of HWI and IQI on conventional NOMA systems. Our analysis assumes that users communicate directly with the source, and we focus on deriving mathematical expressions to quantify these effects over a Rayleigh fading channel. To validate the accuracy of our findings, we conduct comprehensive computer simulations. Subsequently, we explore the synergistic potential of combining NOMA with cooperative communication techniques to enhance spectral efficiency. This novel approach, known as Cooperative NOMA (CNOMA), represents a promising avenue for improving the performance of wireless communication systems. In CNOMA, we consider two distinct concepts: CNOMA without the presence of direct links and CNOMA with direct links between users. In both scenarios, we investigate the influence of various hardware impairments, including HWI and IQI, on critical performance metrics such as BER, OP, and EC. By systematically examining these metrics in the presence of hardware imperfections, we aim to gain a comprehensive understanding of how CNOMA can thrive in real-world conditions, ultimately contributing valuable insights to the field of wireless communications. Finally, the thesis concludes by delving into a comprehensive discussion of the results obtained. It not only highlights the opportunities and challenges revealed but also offers valuable insights that can shape the direction of future research endeavors in this field. \textbf{Keywords:} Bit error rate (BER), Ergodic capacity (EC), Hardware impairment (HWI), Imperfect channel state information (ipCSI), Imperfect successive interference canceler (ipSIC), In-phase and quadrature-phase imbalance (IQI), Non-orthogonal multiple access (NOMA), and Outage probability (OP). فتح التوسع السريع لأنظمة الاتصالات اللاسلكية حقبة جديدة تميزت بالطلب المتزايد على معدلات بيانات أسرع وتقليل زمن الوصول وتحسين الكفاءة الطيفية. لتلبية هذه المتطلبات ، ظهر نظام الوصول المتعدد غير المتعامد NOMA كتقنية تطورية. تسمح NOMA لعدة مستخدمين بمشاركة نفس موارد التردد الزمني ، وبالتالي تحسين قدرة النظام وكفاءته بشكل كبير. كجزء من NOMA ، مجال الطاقة PD-NOMA ، المستخدمين أو تقاسم الموارد مع مختلف معاملات توزيع الطاقة, يثير إريت كثافة العمليات معين. يستخدم هذا النهج أداة إلغاء التداخل المتتالية SICلتقييم التدخلات ويظهر إمكانات كبيرة للتطبيقات في الجيل 5 وما بعده ، مما يؤدي إلى بحث مكثف حول معدلاته القابلة للتحقيق واحتمالات الانقطاع. في أنظمة الاتصالات الحقيقية ، تلعب أجهزة الإرسال والاستقبال دورا محوريا من خلال تسهيل إرسال واستقبال الإشارات. ومع ذلك ، نظرا للطبيعة المعقدة لمكوناتها الداخلية والتعقيد المتأصل في عملية التصنيع ، فمن الشائع جدا أن تظهر أجهزة الإرسال والاستقبال عيوبا في الأجهزة وسلوكا غير مثالي. تؤدي العديد من العوامل المساهمة إلى ظهور هذه العملية غير المثالية ، لا سيما في أجهزة الإرسال والاستقبال ذات التردد اللاسلكيRF. تتجلى هذه الإعاقات في الأجهزة HWIعبر مراحل مختلفة من تشغيل جهاز الإرسال والاستقبال ، والسلوك غير الخطي في مكبرات الصوت عالية الطاقة ، ووجود ضوضاء الطور ، والاختلالات في مكونات الطور والتربيع I/Q داخل الواجهة الأمامية للترددات اللاسلكية. الدافع وراء بحثنا ينبع من اهتمامين رئيسيين: \ {NOMA} و \ {HWI}. يرتكز عملنا على هدف استكشاف وفهم الأداء مثل السعة واحتمالية الانقطاع \ {(OP)} والسعة المريحة \ {(EC)} ومعدل خطأ البت \ {(EC)} لأنظمة \ {NOMA} التي تعمل في وجود \ {HWI}. يسعى هذا البحث إلى توفير ظروف واقعية، حيث يمكن أن تؤثر عيوب الأجهزة بشكل كبير على كفاءة النظام وموثوقيته بشكل عام. ومن خلال معالجة هذه القضايا الحاسمة، تهدف دراستنا إلى المساهمة في تعزيز أنظمة الاتصالات القائمة على \ {NOMA} وتنفيذها العملي في مجموعة من التطبيقات.\\ في الجزء الأول من هذه الأطروحة، نتعمق في تأثير \ {HWI} و \ {IQI} على أنظمة \ {NOMA} التقليدية. يفترض تحليلنا أن المستخدمين يتواصلون مباشرة مع المصدر، ونركز على استخلاص التعبيرات الرياضية لتحديد هذه التأثيرات عبر قناة خبو رايلي. للتحقق من دقة النتائج التي توصلنا إليها، نقوم بإجراء عمليات محاكاة حاسوبية شاملة.\\ وبعد ذلك، نستكشف الإمكانات التآزرية للجمع بين \ {NOMA} وتقنيات الاتصال التعاوني لتعزيز الكفاءة الطيفية. يمثل هذا النهج الجديد، المعروف باسم \ {NOMA} التعاوني \ {(CNOMA)}، وسيلة واعدة لتحسين أداء أنظمة الاتصالات اللاسلكية.\\ في \ {CNOMA}، نعتبر مفهومين متميزين: \ {CNOMA} بدون وجود روابط مباشرة و \ {CNOMA} مع روابط مباشرة بين المستخدمين. في كلا السيناريوهين، نقوم بالتحقيق في تأثير حالات قصور الأجهزة المختلفة، بما في ذلك \ {HWI} و \ {IQI}، على مقاييس الأداء المهمة مثل \ {BER} و \ {OP} و \ {EC}. ومن خلال الفحص المنهجي لهذه المقاييس في ظل وجود عيوب في الأجهزة، فإننا نهدف إلى الحصول على فهم شامل لكيفية ازدهار \ {CNOMA} في ظروف العالم الحقيقي، مما يساهم في النهاية برؤى قيمة في مجال الاتصالات اللاسلكية.\\ وأخيرا، تختتم الرسالة بالخوض في مناقشة شاملة للنتائج التي تم الحصول عليها. فهو لا يسلط الضوء على الفرص والتحديات التي تم الكشف عنها فحسب، بل يقدم أيضًا رؤى قيمة يمكن أن تشكل اتجاه المساعي البحثية المستقبلية في هذا المجال.\\
في العلوم التكنولوجياReseaux et telecommonication أطروحة دكتوراه
Keywords: Bit error rate (BER); Ergodic capacity (EC); Hardware impairment (HWI); Imperfect channel state information (ipCSI); Imperfect successive interference canceler (ipSIC); In-phase and quadrature-phase imbalance (IQI); Non-orthogonal multiple access (NOMA); and Outage probability (OP; معدل خطأ البت \ {(BER)}، السعة المريحة \ {(EC)}، ضعف الأجهزة \ {(HWI)}، معلومات حالة القناة غير الكاملة \ {(ipCSI)}، أداة إلغاء التداخل المتتالي غير الكامل \ {(ipSIC)}، اختلال التوازن في الطور والطور التربيعي \ {(IQI)}، غير - الوصول المتعدد المتعامد \ {(NOMA)}، واحتمال الانقطاع \ {(OP)}